2010
DOI: 10.4103/0019-5049.71039
|View full text |Cite
|
Sign up to set email alerts
|

Complications of regional and general anaesthesia in obstetric practice

Abstract: Any anaesthetic technique, either regional or general, has potential for complications. Moreover, it has been seen that in obstetric patients, the complications are potentiated due to pregnancy-related changes in physiology and due to various other factors. Increasing trend of caesarean section in the setting of increasing maternal age, obesity and other concomitant diseases will continue to challenge the obstetric anaesthetist in his/her task of providing safe regional and general anaesthesia. This review has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
1
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 31 publications
0
33
1
4
Order By: Relevance
“…Hypotension was observed in a few patients in both groups because of preoperative fluid replacement. SA may cause bradycardia [15]. However, in our study, bradycardia was not observed in either group.…”
Section: Discussioncontrasting
confidence: 71%
“…Hypotension was observed in a few patients in both groups because of preoperative fluid replacement. SA may cause bradycardia [15]. However, in our study, bradycardia was not observed in either group.…”
Section: Discussioncontrasting
confidence: 71%
“…Hipotensi yang terjadi dapat diatasi dengan posisi trendelenberg, pemberian cairan melalui kateter intravena, terapi oksigen, dan pemberian obat-obat vasopresor. 5,6 Pemberian dosis kecil anestetik lokal dengan penambahan opioid intratekal dapat meningkatkan potensi analgetika tanpa meningkatkan level blokade simpatis sehingga angka kejadian hipotensi dapat berkurang. 2,7,8 Berdasarkan hasil penelitian tahun 2001 dinyatakan bahwa angka kejadian hipotensi selama anestesia spinal pada seksio sesaria mencapai 80%, meskipun telah dilakukan prehidrasi cairan, posisi uterus miring ke kiri, dan penggunaan vasopresor.…”
Section: Pendahuluanunclassified
“…Range (min-maks) [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] 90 wanita hamil yang dilakukan anestesia spinal untuk tindakan seksio sesarea di RSHS. Pasien dengan status fisik ASA II dan III dengan usia termuda adalah 17 tahun dan tertua 46 tahun (Tabel 1).…”
Section: Tabel 3 Penggunaan Vasopresor Efedrin Jumlah Efedrin (Mg)unclassified
See 2 more Smart Citations